2005
DOI: 10.1016/j.gene.2005.05.015
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of the very large G-protein coupled receptor gene (Vlgr1/Mass1/USH2C) in zebrafish

Abstract: Very Large G-protein coupled Receptor-1 (VLGR1/Mass1/USH2C) is the largest known cell surface protein in vertebrates. Mutations in VLGR1 are associated with audiogenic epilepsy in mice and Usher syndrome (sensorineural deafness and retinitis pigmentosa) in humans. We characterized the zebrafish VLGR1 gene (vlgr1). It is 51% identical to human VLGR1 in amino acid sequence, but is 64% identical in the 7-transmembrane and cytoplasmic domains. It is 6199 amino acids in size and is encoded by a 19.2 kb mRNA. All in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0
1

Year Published

2006
2006
2015
2015

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(12 citation statements)
references
References 31 publications
(35 reference statements)
0
11
0
1
Order By: Relevance
“…The GPR98 gene (also known as VLGR1 or MASS1) encodes for a member of the G-protein-coupled receptors family 2, which are probably involved in cell-cell adhesion. 25 In situ hybridization studies on mouse embryos have shown that GPR98 is highly expressed in the CNS, particularly in the ventricular zone, and likely plays an important role in brain development. 26 Mutations in GPR98 have been found in a family with febrile seizures 27 and have also been described in the Frings mouse, 28 which exhibits audiogenic seizures.…”
Section: Discussionmentioning
confidence: 99%
“…The GPR98 gene (also known as VLGR1 or MASS1) encodes for a member of the G-protein-coupled receptors family 2, which are probably involved in cell-cell adhesion. 25 In situ hybridization studies on mouse embryos have shown that GPR98 is highly expressed in the CNS, particularly in the ventricular zone, and likely plays an important role in brain development. 26 Mutations in GPR98 have been found in a family with febrile seizures 27 and have also been described in the Frings mouse, 28 which exhibits audiogenic seizures.…”
Section: Discussionmentioning
confidence: 99%
“…GPR98/Mass1 is highly expressed in the developing CNS of zebrafish embryos, particularly in the hypothalamus, epiphysis and the rhombic lips. 20 Mouse embryos show a high level of expression restricted to the eyes and the developing CNS, particularly in the ventricular zone, home of neural progenitor cells during embryonal neurogenesis. 21 GPR98/MASS1, a known epilepsy gene, contains both the epilepsy-associated repeat (EAR) and the epitempin (EPTP) repeat.…”
Section: Discussionmentioning
confidence: 99%
“…GPR98 ortholog mRNAs were detected in the mouse and zebrafish brains [67, 169]. VLGR1 protein is highly enriched in the mouse midbrain superior and inferior colliculi [70], while inferior colliculus is known to participate in the occurrence of audiogenic seizures [170].…”
Section: Functional Studies Of Ush Gene Productsmentioning
confidence: 99%